Better outcomes of modified myeloablative conditioning without antithymocyte globulin versus myeloablative conditioning in cord blood transplantation for hematological malignancies: A retrospective (development) and a prospective (validation) study. Issue 3 (12th March 2018) - Sun, Zimin; Liu, Huilan; Luo, Chenhui; Geng, Liangquan; Zheng, Changcheng; Tang, Baolin; Zhu, Xiaoyu; Tong, Juan; Wang, Xingbing; Ding, Kaiyang; Wan, Xiang; Zhang, Lei; et al.
Abstract : Cord blood transplantation (CBT) is an effective option for treating hematological malignancies, but graft failure (GF) remains the primary cause of therapy failure. Thus, based on myeloablative conditioning (MAC) of busulfan with cyclophosphamide (Bu/Cy) or total body irradiation with Cy (TBI/Cy), fludarabine (Flu) was added to Bu/Cy and cytarabine (CA) to TBI/Cy for a modified myeloablative conditioning (MMAC). To compare the prognosis of MMAC with MAC, we conducted a retrospective study including 58 patients who underwent CBT with MAC or MMAC from 2000 to 2011. Neutrophil and platelet engraftment rate, overall survival (OS) and disease free survival (DFS) were significantly higher in the MMAC group (adjusted hazard ratio [HR], 2.58, 2.43, 0.36 and 0.37; p  < 0.01, p  = 0.01, p  = 0.02 and p  = 0.02, separately). Nonrelapse mortality (NRM) was comparable ( p  = 0.183). To validate the outcomes noted in the MMAC group, we conducted a prospective single‐arm clinical trial including 188 patients who underwent CBT with MMAC from 2011 to 2015. Engraftment rate, survival and NRM of the MMAC group in the prospective trail (MMAC‐P) were similar to the MMAC group in the retrospective study (MMAC‐R). This study is the first to demonstrate the superiority of MMAC to MAC in CBT for hematological malignancies. Abstract : What's new? Cord blood transplants can help patients with blood cancer, but too often, the transplant fails due to immune rejection or other problems. Typically, patients receive myeloablative conditioning (MAC) prior to CBT, but more intense regimen might improve transplant success. Here, the authors compared the success of modified myeloablative conditioning (MMAC) with conventional MAC by looking at 58 patients over an 11‐year period. They then followed up with a four‐year prospective study, including 188 patients who received cord blood transplant with MMAC. The modified conditioning regimen boosted graft success and improved survival of patients with hematological cancers.